Shabby Communities. Structural Violence and Less than Obvious Mechanisms that Spoil Science - Kobylarek, Aleksander (Journal of Education Culture and Society, 2024)
Different social groups functioning as authorities for the masses do not fulfil their roles; they represent wrong, often illegal roles and through manipulation, endeavour to attract others to their side. The ones who reveal these activities are seen as independent media and journalists, however, when confronted by the authorities, are revealed not to always have the desired effect of punishing the guilty. A particular case is a scientific environment that does not implement its worthy cause and even renounces it because of pressure from the authorities and/or work environment or simply to pursue its own ambitions, contrary to the very idea of science it claims to represent. Thus, the independence of a researcher and the objectivity of research results are at stake. Some researchers prove their incompetence in areas that should form the basis of their work, such as the English language, the lack of which makes it impossible to promote results internationally and to further the latest developments outside one’s own language area. The elite structures are also often closed, thereby preventing the development of other researchers who could become competitors or alternative opinion holders. The criteria for the evaluation of achievements by being inconsistent becomes hard to question; the key to entering this closed structure thereby seems to be the submissiveness of a researcher, as institutional violence, because of subjective and trivial reasons, puts the skids under development opportunities. The blocking of development and other pathologies in the scientific community are also common in the local communities that still function in spite of their incompetence.